Innovative Low-fouling membranes- an Advanced coating approach using UV-LED polymerisation - Gukelberger, Ephraim; Critelli, Salvatore; Gabriele, Bartolo; Figoli, Alberto; Hoinkis, Jan (Università della Calabria, 2020)
Overcoming hurdles connected with increasing water scarcity exacerbated by climate change is one of the major challenges of this century. Membrane bioreactors (MBR) have been applied for more than two decades improving the water recovery of industrial and domestic wastewater treatment processes and ease this situation. Occurring membrane fouling phenomena pose a massive drawback for achieving a highly efficient filtration in the long run. One fouling mitigation approach is the novel low-fouling membrane coating using a polymerisable bicontinuous microemulsion (PBM). In this thesis, the membrane coating process and the layer polymerisation mainly initiated by UV-LED light was systematically studied. A casting process was evaluated on small scale samples (0.0085 m2) and further developed. For the first time UV-LED light induced PBM coating has been applied on a pilot scale of 3.125 m2 membrane surface area. Studies included the validation of a modified, low cost surfactant to reduce overall synthesis costs. Membrane pore intrusion of the low viscous PBM during the casting coating presented an obstacle to meet competitive filtration capacities compared to commercial ultrafiltration (UF) polyethersulfone (PES) membranes. Viscosity modification towards higher values was studied based on controlled radical polymerisation inhibition. Additionally, a high discrepancy to the pristine PBM coating solution was determined. The development and construction of an automated coating machine enabled high production quantities. Ultimately, the novel coating was tested in a customised pilot MBR for the treatment of domestic wastewater. The pilot tests allowed the direct and simultaneous comparison between a PBM coated and commercial PES module. Short stress tests through a flux step profile and a long-term operation were carried out under constant flux conditions. The PBM coated membrane showed lower permeability with a higher increase in the specific transmembrane pressure (TMP) within a 137-day trial period. Subsequently, post studies validated the chemical stability of the coating material qualitatively. Various experiments revealed limitations for low-strength domestic wastewater application in terms of lower critical flux. Based on these findings, a feasibility study of spray coating technology using two different atomisation approaches on a lab scale was conducted. Spray coating prevents shearing between the casting knife, the liquid PBM and the membrane surface which reduces the pore intrusion effect potentially. Various preliminary spray tests were examined to study the surface coverage along the membrane width in correlation with the given spray parameters. It was shown that there were structural differences of the polymerised coating layers compared to the casting coating techniques. In conclusion, spray coating using duel-fuel nozzles improved the membrane performance. Furthermore, high operation flexibility helped to produce defined spray coverages and layer thickness for any type of coating material as well as membrane substrate. However, some effects remain unclear. This requires a more fundamental study of material properties and atomisation technologies related to polymerisable bicontinuous microemulsions due to complex interactions.
Università della Calabria. Dipartimento di Ingegneria per l'Ambiente e il Territorio e Ingegneria Chimica. Dottorato di ricerca in Scienze e Ingegneria dell'Ambiente, delle Costruzioni e dell'Energia. Ciclo XXXII
Keywords: Research Subject Categories::NATURAL SCIENCES::Chemistry::Organic chemistry::Polymer chemistry